MICROORGANISMS AND Î±-AMYLASE: A CONCISE REVIEW - Paul, Dipak (Innovare Journal of Sciences, 2016)
Amylases are one of the most industrially important enzymes and hold the maximum market share of enzyme sales. The article surveys the Î±-amylase family and the major structural characteristics, microbial sources, and industrial applications. This review is therefore, an attempt to execute a detailed study of the literature on the development made in research on microbial Î±-amylase production, a highly important and demanded industrial enzyme in different fields such as starch processing, detergent, alcohol, textile, food, paper, pharmaceutical etc.